PENGEMBANGAN E-MODUL BERBASIS ADOBE FLASH PADA POKOK BAHASAN SISTEM REPRODUKSI UNTUK KELAS IX MIPA SMA - Elma Ayu Permatasari; Imam Mudakir; Kamalia Fikri (FKIP Universitas Jember, 2017)
The study was aimd to develop a valid, practical, and effective E-Module based on Adobe flash. This research was development research. Data collection techniques used questionnaire analysis, pre-test/post-test, student response questionnaire, and validation from the experts. The design of the research is development E-module based on Adobe Flash media using a 4-D model (Define, Design, Develop, Disseminate) that developed by Thiagarajan (1974). The results indicated that the level of validity of developed E-Module based on Adobe Flash was 82.54%, 83.89% , 79.58%, based on experts of subject, media and media development respectively, while developed media validity according to teacher as user was 88,93%, practical was 91,11%, effective was 0,72.